2012
DOI: 10.1021/ja309317u
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous CO2 Reduction at Very Low Overpotential on Oxide-Derived Au Nanoparticles

Abstract: Carbon dioxide reduction is an essential component of many prospective technologies for the renewable synthesis of carbon-containing fuels. Known catalysts for this reaction generally suffer from low energetic efficiency, poor product selectivity, and rapid deactivation. We show that the reduction of thick Au oxide films results in the formation of Au nanoparticles ("oxide-derived Au") that exhibit highly selective CO(2) reduction to CO in water at overpotentials as low as 140 mV and retain their activity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

81
1,466
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,569 publications
(1,557 citation statements)
references
References 24 publications
81
1,466
3
7
Order By: Relevance
“…d) Cross‐sectional SEM image and e) high‐magnification TEM image of oxide‐derived Au NPs; f) Faradaic efficiency for CO and formate on oxide‐derived Au NPs in 0.5 m NaHCO 3 . Reproduced with permission 65. Copyright 2012, American Chemical Society.…”
Section: Electrocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…d) Cross‐sectional SEM image and e) high‐magnification TEM image of oxide‐derived Au NPs; f) Faradaic efficiency for CO and formate on oxide‐derived Au NPs in 0.5 m NaHCO 3 . Reproduced with permission 65. Copyright 2012, American Chemical Society.…”
Section: Electrocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…Kanan and co‐workers prepared oxide‐derived Au by simply applying a periodic square‐wave potential routine on Au electrodes and then electrochemically reducing thick Au oxide films (Figure 6d–f) 65. It was suggested that unique metastable structures were resulted from the reduction of the oxide film.…”
Section: Electrocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single-step electrochemical process that can directly convert CO 2 to methane under conditions of ambient pressure and temperature may represent an attractive alternative. Of the metals explored as catalysts for electrochemical CO 2 reduction,(8) the most active and selective identified to date are gold, silver, and bismuth, (9)(10)(11)(12)(13)(14) which produce CO as their terminal product. Copper is attractive in comparison, as it produces more reduced hydrocarbon products.…”
mentioning
confidence: 99%
“…It was shown that the surface chemicalc omposition of the Sn foil plays ac rucial role in dictating the conversion of CO 2 into HCOO À . [113] When the native oxide layer in Sn foil was etchedo ut by using concentrated acid, the subsequent electrode demonstrated quite low FE HCOO À compared to the pristine Sn foil (containing native oxide layer). This finding highlighted the requirement of ah eterojunction (interface) between the different oxidation states of Sn for CO 2 RR to HCOO À .T his understanding was also invoked with novel nanostructures such as heat-treatedS nd endrite, which displayed a7 1.6 %F E HCOO À at an applied potential of À1.36 Vi nc omparison with the untreated Sn dendrite, which only exhibited 57 %F E HCOO À at the same potential.…”
Section: Snmentioning
confidence: 99%